SONIQO-16 - Ingvarsson,Herman (2025)
This project explores how a beginner friendly music production device can lower the threshold for engaging with sound creation and rhythm making. Many existing tools rely on prior knowledge or technical skill, which discourages new users from experimenting in creative ways. This project instead focuses on quick feedback, clear interaction and a tactile experience that invites curiosity and play. Through hands on prototyping, research and testing a standalone device was designed with sixteen pads, physical knobs and a responsive interface that guides users through the basics of sequencing and sound shaping. The aim was to create an intuitive and portable tool that makes the process of creating electronic music feel accessible, motivating and enjoyable from the very first use. With a focus on physical feedback and minimal digital complexity, the product encourages users to explore music through touch, helping them gain confidence without needing traditional training or computer based software.
Keywords: based Input Sound Design Tool Real-time Audio Interaction Sensor-based Input Music Hardware Prototyping Digital Musical Instruments Tangible User Interface Accessible Music Technology Analog Digital Hybrid Expressive Interaction Embedded Design Design for Beginners Educational Music Tools